1992
DOI: 10.1042/bj2830075
|View full text |Cite
|
Sign up to set email alerts
|

Purification and characterization of polyamine oxidase from Ascaris suum

Abstract: The interconversion of polyamines in the parasite nematode Ascaris suum by a novel type of polyamine oxidase was demonstrated. The nematode enzyme was clearly distinguishable from monoamine and diamine oxidases as well as from the mammalian polyamine oxidase, as shown by the use of the specific inhibitors pargyline, aminoguanidine and MDL 72527 respectively. All three inhibitors had no effect on the parasite polyamine oxidase, and the enzyme did not accept diamines such as putrescine, cadaverine or histamine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Thus, under these circumstances, the induction of polyamine oxidases is an adaptation to the environment [16] and this may also be the case in some helminths [23] and other parasites [24,25]. …”
mentioning
confidence: 99%
“…Thus, under these circumstances, the induction of polyamine oxidases is an adaptation to the environment [16] and this may also be the case in some helminths [23] and other parasites [24,25]. …”
mentioning
confidence: 99%
“…Although free-living nematodes possess ODC (Macrae et al 1995;von Besser et al 1995), parasitic nematodes appear to lack ODC activity and, thus, are dependent on polyamine uptake and polyamine interconversion for their supply of polyamines (Wittich et al 1987;Walter 1988;Sharma et al 1991). In Ascaris suum, a convenient model for filarial parasites, polyamine oxidase is the rate-limiting enzyme of polyamine interconversion (Müller and Walter 1992). Using MDL 72527 [N,N′-2, 3(bisbutadienyl)-1, 4 butanediamine], a specific inhibitor of mammalian tissue polyamine oxidase, Seiler (1987) has shown that polyamine oxidase has no regulatory function in mammalian cells.…”
mentioning
confidence: 99%
“…Polyamine oxidase from A. suum was isolated as previously described (Müller and Walter 1992), and for inhibition studies the enzyme was pre-incubated with different concentrations of inhibitors for 10 min before aliquots were assayed for polyamine oxidase activity in a standard assay mixture. The results are summarized in Table 1.…”
mentioning
confidence: 99%
See 2 more Smart Citations